Sustainable Ecotourism and Creative Economy Development Model with Local Wisdom Perspective - ROZARI, Petrus Emanuel de ROZARI; POLINGGOMANG, Yoseba; FANGGIDAE, Apriana H. J. (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to profile ecotourism and the creative economy from a local wisdom perspective, analyze and design their development models, and identify supporting and inhibiting factors. The research employs qualitative data analysis in Alor Regency, East Nusa Tenggara Province. Findings reveal that Alor Regency's ecotourism and creative economy boast unique diversity, offering significant local economic and welfare enhancement potential. Despite adopting sustainable community-based tourism, the development model's implementation and sustainability remain unclear. Two proposed models suggest a dominant community role with private partners or a private sector-led approach involving the community. Supporting factors include Alor's designation as a National Tourism Strategic Area in Ripparnas. However, several inhibiting factors hinder development, such as the inadequate quality and service standards of tourist attractions, insufficient facilities and infrastructure, low human resource quality, and issues with standardization, promotion, and institutions. To address these challenges, a shift in perspective is necessary, along with strategic planning targeting long-term, medium-term, and short-term goals. A joint commitment among stakeholders is also essential for sustainable development.